Reduction of oxygen in a trialkoxy ammonium-based ionic liquid and the role of water. (1st April 2016) - Pozo-Gonzalo, Cristina; Kar, Mega; Jónsson, Erlendur; Howlett, Patrick C.; MacFarlane, Douglas R.; Forsyth, Maria
Graphical abstract: Highlights: Effect of Electrode material on the oxygen reduction has been studied in a novel trialkoxy based-IL. Gold presented slower electrokinetics due to stronger adsorption energy with the IL. Upon water addition, a reversible 2-electron reduction process has been attained. Abstract: The oxygen reduction reaction in a novel trialkoxy ammonium-based ionic liquid, N-ethyl-2-(2-methoxyethoxy)-N, N-bis(2-(2-methoxyethoxy)ethyl)ethan-1-aminium bis(trifluoromethylsulfonyl)imide, [N2(20201)(20201)(20201) ] [NTf2 ] has been studied on glassy carbon and gold electrodes, showing faster electrokinetics on glass carbon because of weaker adsorption of the IL. This has been demonstrated by theoretical calculations and electrochemical studies. In the neat IL, the oxygen is reduced to superoxide (O2 − ) through a one electron process; however, better performance is attained in the presence of water (42 mol%), in terms of current density, and onset potential of the reduction process via a reversible 2-electron process. Furthermore, a remarkable increase in cyclic coulombic efficiency is observed for the wet IL (66% in comparison with the neat IL (24%), showing the practicality of a reversible O2 /H2 O2 system for energy storage.